The Effectiveness of Using Canva Application as A Science Learning Media in Elementary Schools - Susanti, Dyah Aris; Sultonurohmah, Nina; Purwitasari, Eva Dewi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
This study aims to analyze the effectiveness of using the Canva application as a learning medium in science subjects at elementary schools through a literature review method. The data used are secondary data obtained from various journals, scientific articles, and conference proceedings. The analysis of six scientific works indicates that the use of Canva has a positive impact on increasing students' learning motivation, academic performance, and creativity. Canva's features, which allow the creation of interactive learning media such as videos and visualizations of abstract concepts, facilitate educators in delivering material. Additionally, Canva helps enhance students' science literacy by presenting engaging content aligned with 21st-century technological advancements. The platform is also considered practical and user-friendly for teachers, requiring no special design skills. However, some limitations were identified in its application, such as the frequent combination of Canva with other learning media and suboptimal implementation in online learning. In conclusion, Canva is an innovative, effective, and relevant learning tool to improve the quality of science education in elementary schools.